Status and Developing Strategies for Neutralizing Monoclonal Antibody Therapy in the Omicron Era of COVID-19 - Ren, Zuning; Shen, Chenguang; Peng, Jie (Viruses, 2023)
The monoclonal antibody (mAb)-based treatment is a highly valued therapy against COVID-19, especially for individuals who may not have strong immune responses to the vaccine. However, with the arrival of the Omicron variant and its evolving subvariants, along with the occurrence of remarkable resistance of these SARS-CoV-2 variants to the neutralizing antibodies, mAbs are facing tough challenges. Future strategies for developing mAbs with improved resistance to viral evasion will involve optimizing the targeting epitopes on SARS-CoV-2, enhancing the affinity and potency of mAbs, exploring the use of non-neutralizing antibodies that bind to conserved epitopes on the S protein, as well as optimizing immunization regimens. These approaches can improve the viability of mAb therapy in the fight against the evolving threat of the coronavirus.